Does corporate social responsibility affect earnings management? Evidence from the Indonesian banking industry - Doddy Setiawan; Ronny Prabowo; Vina Arnita; Anas Wibawa (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
This paper aims at examining the effect of corporate social responsibility on earnings management in the Indonesian banking industry. Using Indonesian publicly listed banking firms in the years of 2013-2015 as the sample, we generate 94 firmyear observations as the final sample. The results show that corporate social responsibility positively affects earnings management, suggesting that the higher the corporate social responsibility score, the greater earnings management. Further, the study investigates the effects of corporate social responsibility on absolute earnings management, positive earnings management, and negative earnings management. The results robustly demonstrate the positive effects of corporate social responsibility on earnings management. Thus, this study implies that investors need to be cautious of banks that engage in higher corporate social responsibility because they are more likely to exhibit greater earnings management. While most of the previous studies in this issue focus on developed countries as their research settings, this study provides empirical evidence on the relationship between corporate social responsibility in Indonesia as an emerging market.
Keywords: M41; G21; 650; corporate social responsibility; earnings management; discretionary accrual; banking; disclosure; Indonesia